Outcomes of Pregnancies in Women with Congenital Heart Disease: A Study in a Tertiary Care Hospital in Bangladesh (Journal of Rangpur Medical College, 2024)
Background: Pregnancies in individuals with congenital heart disease (CHD) frequently pose complex challenges. The presence of CHD elevates the risks not only for the expectant mother but also for the well-being of the developing fetus. Additionally, careful monitoring and specialized medical care are crucial throughout the pregnancy to ensure the best possible outcomes for both. Objective: This study was aimed to assess the outcomes of pregnancies in women with congenital heart disease. Methods: This was a cross-sectional observational study that was conducted in the Combined Military Hospital (CMH), Dhaka, Bangladesh from January 2020 to December 2021. A total 30 pregnant women with congenital heart disease were enrolled through purposive sampling. All the demographic and clinical information was recorded. Data were processed, analyzed, and disseminated by using MS Office tools. Results: Among participants, Lower Segment Cesarean Section (LSCS) was the most common delivery (43.3%), followed by vaginal delivery (36.7%). Instrumental delivery, specifically through outlet forceps, was found in 6.7% of cases. Pregnancy termination occurred in 6.7% due to inevitable abortion and 3.3% for medical reasons, resulting in one maternal death (3.3%). Perinatal outcomes included 90% live births and 81.5% with Apgar scores ≥9. Neonatal Intensive Care Unit (NICU) admission was required for 33.3%, with a 3.3% perinatal death rate. Conclusions: In pregnant women with congenital heart diseases, common delivery modes are Lower Segment Cesarean Section (LSCS) and vaginal delivery. Termination and maternal fatality rates are low. Perinatal outcomes are generally positive, with most births resulting in live infants with Apgar scores ≥9 and high newborn survival rates, although some require Neonatal Intensive Care Unit (NICU) admission.J Rang Med Col. March 2024; Vol. 9, No. 1: 50-54